2008
DOI: 10.1016/j.matbio.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

TSG-6 binds via its CUB_C domain to the cell-binding domain of fibronectin and increases fibronectin matrix assembly

Abstract: Human plasma fibronectin binds with high affinity to the inflammation-induced secreted protein TSG-6. Fibronectin binds to the CUB_C domain of TSG-6 but not to its Link module. TSG-6 can thus act as a bridging molecule to facilitate fibronectin association with the TSG-6 Link module ligand thrombospondin-1. Fibronectin binding to TSG-6 is divalent cation-independent and is conserved in cellular fibronectins. Based on competition binding studies using recombinant and proteolytic fragments of fibronectin, TSG-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 32 publications
1
39
1
Order By: Relevance
“…Downregulation of CSMD1 expression in MCF10A cells decreased adhesion to Matrigel and fibronectin. The stimulatory role of CSMD1 in cell-matrix adhesion is consistent with the effects of other structurally similar proteins such as neuropilin-1 (33), bone morphogenetic protein 1 and TNF-stimulating gene 6 (34,35) in this process.…”
Section: Discussionsupporting
confidence: 73%
“…Downregulation of CSMD1 expression in MCF10A cells decreased adhesion to Matrigel and fibronectin. The stimulatory role of CSMD1 in cell-matrix adhesion is consistent with the effects of other structurally similar proteins such as neuropilin-1 (33), bone morphogenetic protein 1 and TNF-stimulating gene 6 (34,35) in this process.…”
Section: Discussionsupporting
confidence: 73%
“…7 Recently, it is reported that some type of CUB domain binds to fibronectin and modulates interaction of the other matrix components. 21 Moreover, CDCP1 interacts with a number of adhesion and matrix proteins including cadherins and syndecans. 6 It is also proposed that special subsets of integrin affect phosphorylation of CDCP1.…”
Section: Discussionmentioning
confidence: 99%
“…Protein TSG6 is not constitutively expressed in normal adult tissue but rather in inflammatory or inflammatory-like circumstances such as ovulation (18 -20). By its link module, TSG6 can bind many substances such as glycosaminoglycan, including HA, to modulate the tissue microenvironment (21,22). Heavy chains of inter-␣-inhibitor (I␣I) and HA were shown to form covalent complexes in the knee joint with rheumatoid arthritis (23).…”
mentioning
confidence: 99%